2021
DOI: 10.1152/physrev.00026.2020
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and metabolic functions of mTORC1 and mTORC2

Abstract: Cells metabolize nutrients for biosynthetic and bioenergetic needs to fuel growth and proliferation. The uptake of nutrients from the environment and their intracellular metabolism is a highly controlled process that involves crosstalk between growth signaling and metabolic pathways. Despite constant fluctuations in nutrient availability and environmental signals, normal cells restore metabolic homeostasis to maintain cellular functions and prevent disease. A central signaling molecule that integrates growth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
255
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 348 publications
(302 citation statements)
references
References 543 publications
3
255
0
Order By: Relevance
“…In our previous studies, we reported an increase in the mTORC1 and mTORC2 activity in cerebral ischemia-reperfusion where there is a shortage of energy and an imbalance between energy demand and metabolism (Chi et al, 2016a(Chi et al, , 2020Weiss et al, 2018). In this study, the phosphorylation of Akt ( Ser473) is increased during ischemiareperfusion of the brain of the rat, which is consistent with the role of mTORC2 in responding to starvation conditions and neuronal survival through FOX03a (Brunet et al, 2001;Szwed et al, 2021). The elevated phosphorylation of Akt (Ser473) during ischemia-reperfusion is accompanied by increased mTORC1 signaling.…”
Section: Figure 3 | (A)supporting
confidence: 89%
See 1 more Smart Citation
“…In our previous studies, we reported an increase in the mTORC1 and mTORC2 activity in cerebral ischemia-reperfusion where there is a shortage of energy and an imbalance between energy demand and metabolism (Chi et al, 2016a(Chi et al, , 2020Weiss et al, 2018). In this study, the phosphorylation of Akt ( Ser473) is increased during ischemiareperfusion of the brain of the rat, which is consistent with the role of mTORC2 in responding to starvation conditions and neuronal survival through FOX03a (Brunet et al, 2001;Szwed et al, 2021). The elevated phosphorylation of Akt (Ser473) during ischemia-reperfusion is accompanied by increased mTORC1 signaling.…”
Section: Figure 3 | (A)supporting
confidence: 89%
“…Mechanistic target of rapamycin (mTOR), as a catalytic subunit of two distinct protein complexes, namely, rapamycin-sensitive mTORC1 and rapamycin-insensitive mTORC2, is a protein kinase and an integral regulator of cellular proliferation, apoptosis, growth, metabolism, and autophagy (Murugan, 2019 ; Szwed et al, 2021 ). Both mTORCs are involved in maintaining metabolic homeostasis by responding to intracellular and environmental nutrient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This observation agrees with other studies ( 14 , 15 , 16 , 17 , 18 ), several of which reported that TBK1 phosphorylates Akt S473 directly ( 16 , 17 , 18 ). As Akt S473 represents an established target of mTOR complex 2 (mTORC2) ( 19 , 20 , 21 , 22 ), we investigated more fully the mechanism by which TBK1 promotes Akt phosphorylation, testing the hypothesis that TBK1 directly activates mTORC2 and its downstream signaling to Akt.…”
mentioning
confidence: 99%
“…mTOR comprises the catalytic kinase core of two known multisubunit mTOR complexes (mTORCs) ( 21 , 22 , 23 ). The scaffolding protein Raptor (regulatory-associated protein of mTOR) defines mTORC1 ( 24 , 25 ), whereas the scaffolding protein Rictor (rapamycin-insensitive companion of mTOR) defines mTORC2 ( 26 , 27 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation